Accident and sickness insurance for children of farmers insured in the Agricultural Social Insurance Fund - Puślecki, Damian (Przegląd Prawa Rolnego, 2020)
The article provides an answer to the question to what extent economic insurance provides protection against the effects of accidental events to children who help their parents in agricultural activity. It compares the scope of protection granted in insurance for children against the consequences of accidents and certain diseases with the solutions adopted in agricultural social insurance. As has been found, despite the small advantage in some aspects of protection, the group economic insurance cannot provide adequate protection for children if they become unable to work. The insurance does not sufficiently perform a preventive function, and the amount of health benefits obtained is much lower than those paid by the Agricultural Social Insurance Fund. However, in the absence of any other option, children working in agriculture may count on at least a substitute for insurance protection. Yet, economic insurance should have a supporting character, supplementing the scope of protection provided by the agricultural social insurance scheme.